Improving the effectiveness of obesity treatment by combining a diet and motivational techniques - Patrycja Kłósek; Sebastian Grosicki; Beata Całyniuk (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Obesity is considered a disease. The treatment of obesity should include the modification of health behaviors in order to achieve long-term weight loss. Objectives. The comparison between traditional weight loss treatment with and without a motivational therapy. Materials and Methods. The study included 104 overweight women or women with obesity with a median age of 34. They were under the supervision of a dietician. The patients were divided into two groups: the standard group which was on an individualized and low-calorie diet developed by a dietitian and received substantial support, and the study group which additionally used motivational techniques. Results. Mean weight loss, mean reduction in waist measurement and body fat after a 5-month treatment were calculated. The mean body weight loss in control group was 10.56 kg (± 8.65), the waist measurement was 11.84 cm (± 10.62), and fat loss was 5.11 (± 3.17) kg on average - it corresponds to 8.02% (±6.55). The study in which additional motivational techniques were used, the mean weight loss was 17.31 kg (± 9.29), the waist measurement was 15.25 cm (± 8.28), and fat loss was 8.34 kg - it corresponds to 12.19% (± 7.32) of adipose tissue. All the differences between treatment results in both groups were statistically significant (p <0.05). Conclusions. The dietary treatment process employing motivational techniques has greater therapeutic efficacy than a traditional approach.